Trends in Digital Adoption for Enhancing the Global Performance of SMES: a Bibliometric Analysis - Siti Aulia Majidah A. Sasli; Lissa Rosdiana Noer (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Small and medium-sized enterprises (SMEs) play a vital role in the global economy. However, increasing market dynamism has pushed many businesses to move away from traditional approaches and adopt digitalization to enhance their competitiveness. This study aims to map, identify patterns, and analyze the development of literature related to the adoption of digitalization in the behavior, capabilities, and performance of SMEs on a global scale. Relevant articles were retrieved from the Scopus database, covering the period from 2020 to 2025, resulting in 154 documents filtered based on specific criteria. These articles were classified and visualized using the VOSviewer software. The study explores research trends based on documents, authors, sources, and analyzes bibliographic coupling. The findings provide a systematic overview of thematic focuses, interconnections among studies, and potential research gaps in the literature on SME digitalization, which offering a solid foundation for future research in the field of global digital business strategy.